The Role of Innovation Intermediaries in Developing Healthcare Innovation Ecosystems: Value Co-Creation through Platforms - Ngongoni, Chipo Nancy (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.